POLITICS, UNIVERSITY AND SOCIETY IN PUEBLA: THE ASCENT OF MEXICAN COMMUNIST PARTY IN THE UAP, 1970-1972 (2012)
In 1972, members of the Mexican Communist Party took over the leadership of Universidad Autónoma de Puebla. The purpose of this article is to both describe and analyze the process by which they immediately came to power, considering the political speech that influenced them and the cyclical problem of overcrowding, more links with the University of social mobilization and also its conflict with the Groups of local power. The materials that will serve as the reference are archival documents, library records and literature news.